Information System for Purchasing and Sales of Goods on an Android Mobile based E-Store Application - Muhamad Alda; Tursina Juliani Dlt; Lili Saputri; Mirna Annifah Hsb (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to create an information system for purchasing goods on an Android mobile-based e-shop application. Android mobile-based e-shop applications have various advantages, such as making stock management, sales and bookkeeping easier. Additionally, integration with online payments and transaction tracking can improve operational efficiency. The system development method used is Waterfall with an SDLC approach. This research produces an information system for purchasing goods on an Android mobile-based e-shop application, namely dashboard menu, login menu, register menu, about menu, stock of goods, transactions and report menu.